2020
DOI: 10.3390/jcm9082660
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Effect and Feasibility of Percutaneous SI-Screw with and without Augmentation—A 15-Year Retrospective Analysis on over 640 Screws

Abstract: Background: Minimally invasive sacroiliac-screw (SI-screw) fixation of the pelvis is used in energy trauma (Arbeitsgemeinschaft für Osteosynthesefragen (AO) classified) and fragility fractures (Fragility Fracture of the Pelvis (FFP) classified). However, available clinical data are based on small case series and biomechanical data seem to be contradictory. Methods: The present single center retrospective cohort study investigated percutaneous SI-screw fixation and augmentation over 15 years. Groups were compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 45 publications
(71 reference statements)
1
35
1
3
Order By: Relevance
“…Re-establishing mobility with as little additionally morbidity as possible, as well as shorter duration of the surgical procedures, are both crucially important [ 8 ]. It has been shown that the percutaneous SI screw insertion is a safe and effective surgical procedure for stabilisation of the posterior pelvic ring [ 20 ]. However, there is insufficient evidence in the literature for the superiority of one the literature for the superiority [ 8 ], and it remains unclear whether simultaneous stabilisation of the anterior pelvic ring should be performed in anterior and posterior pelvic ring injuries [ 9 ], although this is recommended from a clinical point of view [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Re-establishing mobility with as little additionally morbidity as possible, as well as shorter duration of the surgical procedures, are both crucially important [ 8 ]. It has been shown that the percutaneous SI screw insertion is a safe and effective surgical procedure for stabilisation of the posterior pelvic ring [ 20 ]. However, there is insufficient evidence in the literature for the superiority of one the literature for the superiority [ 8 ], and it remains unclear whether simultaneous stabilisation of the anterior pelvic ring should be performed in anterior and posterior pelvic ring injuries [ 9 ], although this is recommended from a clinical point of view [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moderne operative Techniken, wie z. B. die Zementaugmentation bei sakroiliakaler Verschraubung nach Beckeninsuffizienzfraktur erlauben außerdem eine frühzeitige Mobilisierung und beugen zusätzlich einem Delir vor [ 10 , 24 ].…”
Section: Interdisziplinäre Delirprävention In Der Alterstraumatologieunclassified
“…Full weight bearing mobilization and pain reduction are the goals of the treatment of fragility fractures of the pelvis [6,7]. Several treatment options for posterior pelvic ring fractures are described [8][9][10]. Fixation of sacrum fractures with a percutaneous sacroiliac (SI) screw is widely accepted as standard of care treatment of posterior ring fractures [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several treatment options for posterior pelvic ring fractures are described [8][9][10]. Fixation of sacrum fractures with a percutaneous sacroiliac (SI) screw is widely accepted as standard of care treatment of posterior ring fractures [9,11]. However, SI screw loosening occurs in up to 20% of the cases [12,13].…”
Section: Introductionmentioning
confidence: 99%